Creating with AI: On recent debates about authorship revisiting the influence of Barthes and Foucault - Iulia-Dana PUȘCAȘU (Studia Universitatis Babeș-Bolyai. Philosophia, 2024)
Artificial Intelligence (AI) models are now capable of producing artifacts that mimic human creation, such as visual art, text or music. The remarkable sophistication of these results reignited the debate on authorship, calling into question issues such as intent, originality, autonomy or aesthetic engagement. I will present and explain the main positions on authorship that have emerged from this questioning, drawing on Emanuele Arielli’s recent account in AI-aesthetics and the artificial author (2023). Furthermore, I will show how Roland Barthes’ The Death of the Author (1967) and Michel Foucault’s What is an Author? (1969) are central to understanding the philosophical implications of the debate and how conceptualisations pursued in these works inform current perspectives on authorship when AI is involved.